Synthesis and phase transformation of NaGdF4:Yb–Er thin films using electro-deposition method at moderate temperatures. Issue 43 (15th October 2018) - Jia, Hong; Zhou, Yiping; Li, Xue; Li, Yan; Zhang, Weiying; Fu, Hongzhi; Zhao, Jianguo; Pan, Liuzhan; Liu, Xiaofeng; Qiu, Jianrong
Abstract : Herein, a thin film of hexagonal-phase NaGdF4 :Yb–Er is fabricated by electro-deposition at moderate temperatures. The phase of NaGdF4 :Yb–Er thin film can be controlled by adding PVP in the electrolyte. Abstract : NaGdF4 is considered to be one of the efficient hosts for up-conversion (UC) materials; in particular, rare earth-doped hexagonal-phase NaGdF4 exhibits strong upconversion luminescence. However, thin films of NaGdF4 are difficult to prepare by conventional methods due to the presence of fluorine, and hexagonal-phase NaGdF4 cannot be obtained easily at low temperatures. Herein, a thin film of hexagonal-phase NaGdF4 :Yb–Er is fabricated by electro-deposition at moderate temperatures. More importantly, the phase of NaGdF4 :Yb–Er thin film can be controlled to enhance upconversion luminescence by adding polyvinylpyrrolidone (PVP) in the electrolyte. Upon excitation using a 980 nm diode laser, the UC emission intensity of hexagonal thin films increases significantly compared with that of cubic films. The results pave a new way to control the phase of fluoride crystal films that may find potential applications in photovoltaic devices.